A PROGRAMED ADJUSTMENT PROCEDURE. - Noehl, James W. (The Accounting Review, 1964)
The article presents a simple procedure for teaching accounting adjustments. The use of this procedure will result in better student comprehension of adjustments and provide him with a device for consistently doing adjustments correctly. The article informs that present methods of teaching adjustments account by account, one adjustment at a time, is poor utilization of time and abilities. The procedure to be presented, when initiated on the accounting level detailed below, requires a minimum of memorization and class time. The student's accounting knowledge should have progressed through a simple accounting cycle of recording, posting, closing, and statement preparation. This presumes an elementary knowledge of the various accounts: statement classification, normal balance debit or credit, an account description of what it represents, the basic business transactions that increase or decrease the account balance, and the closing entry if applicable. In addition to the accounting cycle and account characteristics above, knowledge of the procedure to balance a ledger account is needed to present programmed adjustments.